2007
DOI: 10.1002/adsc.200600475
|View full text |Cite
|
Sign up to set email alerts
|

New Ruthenium Catalysts for Asymmetric Transfer Hydrogenation of Prochiral Ketones

Abstract: Tridentate N,N,N-pyridinebisimidazolines have been studied as new ligands for the enantioselective transfer hydrogenation of prochiral ketones. High yields and excellent enantioselectivity up to > 99 % ee have been achieved with an in situ generated catalytic system containing dichlorotris(triphenylphosphine)ruthenium and 2,6-bis-([4R,5R]-4,5-diphenyl-4,5-dihydro-1H-imidazol-2-yl)-pyridine (3a) in the presence of sodium isopropoxide.Keywords: asymmetric transfer hydrogenation; ketones; phosphines; ruthenium; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…[8c, 10b] In recent years, we and others [16] demonstrated the usefulness of monodentate ligands derived from the binaphthophosphepine backbone in asymmetric hydrogenations, [17] transfer hydrogenations, [18] and hydroformylations. [19] Although the potential of chiral monodentate ligands for hydrosilylation reactions has been pointed out in several reviews, [20] to the best of our knowledge there is no reported example of such a copper-catalyzed reaction.…”
mentioning
confidence: 99%
“…[8c, 10b] In recent years, we and others [16] demonstrated the usefulness of monodentate ligands derived from the binaphthophosphepine backbone in asymmetric hydrogenations, [17] transfer hydrogenations, [18] and hydroformylations. [19] Although the potential of chiral monodentate ligands for hydrosilylation reactions has been pointed out in several reviews, [20] to the best of our knowledge there is no reported example of such a copper-catalyzed reaction.…”
mentioning
confidence: 99%
“…As the bulkiness of the substituents decreased from bromo to chloro, the resultant enantioselectivity decreased from 95% to 93% (entries 4 and 5, Table 3). We have previously shown that a benzimidazolyl N-H in a ligand can accelerate the TH and ATH of ketones [28][29][30], and an imidazolinyl N-H functionality has also been reported as improving the enantioselectivity in ATH [38]. In our case, the combination of the two N-H functionalities may provide the complex catalysts with high catalytic activity and good selectivity for ATH of ketones under mild conditions.…”
Section: Asymmetric Transfer Hydrogenation Of Ketonesmentioning
confidence: 83%
“…Chiral imidazolines have been used in a number of applications in asymmetric synthesis [33], among which bidentate phosphine imidazolines have been used in the enantioselective hydrogenation of olefins [34] and allylic substitutions [35], tridentate benzene-bis(imidazolinyl) palladium complexes in asymmetric aza-Morita-Baylis-Hillman reactions [36] and Friedel-Crafts alkylations [37], and pyridinebisimidazoline NNN ligands in ATH [38], asymmetric epoxidation [39] and Henry reactions [40]. Herein, we report the synthesis of Ru(II) complexes bearing a tridentate NNN ligand containing benzimidazolyl and imidazolinyl moieties.…”
Section: Introductionmentioning
confidence: 99%
“…All the major alcohol products had an R configuration, the highest final TOF value was 14850 h À1 (Table 3, entry 7). Notably, Ru II complexes bearing a PhPybox [18] or a chiral bis(2-imidazolyl)pyridine ligand [19] exhibited much lower catalytic efficiency than 13 b in the asymmetric transfer hydrogenation of aromatic ketones.…”
Section: A C H T U N G T R E N N U N G [Min]mentioning
confidence: 99%